Case Study of Successful Utilization of Digital Technology Innovations Determinants of Cooperative Institutions in Bali: The Impact of the Covid-19 Pandemic - Surya Dewi Rustariyuni (International Journal of Applied Business and International Management, 2022)
The Covid-19 pandemic has caused serious problems for all sectors and financial institutions, including cooperatives. One solution for cooperative institutions is to innovate digital technology to overcome social distancing. Cooperatives that can maintain their performance during the Covid-19 pandemic are those that can innovate technology. In this study, a qualitative descriptive method was used to determine the factors that influence the successful use of digital technology innovations by cooperatives in Bali due to the Covid-19 pandemic. The key informants in this study were the chairman of the board and cooperative management who applied digital technology innovation during the Covid-19 pandemic and triangulation was used for data analysis purposes. We found that top management commitment and support, perceived costs, security concerns, compatible technology facilities, perceived benefits, performance expectations and business prospects were critical to the successful use of digital technology innovations by cooperatives in Bali during the Covid-19 pandemic.